Effect of work boot shaft stiffness and sole flexibility on lower limb muscle activity and ankle alignment at initial foot-ground contact when walking on simulated coal mining surfaces: Implications for reducing slip risk. (November 2019) - Dobson, Jessica A.; Riddiford-Harland, Diane L.; Bell, Alison F.; Wegener, Caleb; Steele, Julie R.
Abstract: Design features of safety work boots have the potential to influence how underground coal miners' feet interact with the challenging surfaces they walk on and, in turn, their risk of slipping. Despite the importance of work boot design in reducing the risk of miners slipping, limited research has investigated how boot design features, such as shaft stiffness and sole flexibility, affect the way miners walk. Therefore, this study aimed to investigate the effects of systematic variations to boot shaft stiffness and sole flexibility on lower limb muscle activity and ankle motion in preparation for initial foot-ground contact when 20 males walked across two simulated coal mining surfaces under four mining boot conditions. It was concluded that a boot which has different flexibility and stiffness between the shaft and sole is a better design option to reduce underground coal miners' slip risk than a boot that has a stiff shaft and stiff sole or flexible shaft and flexible sole. Highlights: Shaft stiffness and sole flexibility are important design features of work boots. 20 males walked across 2 simulated mining surfaces under 4 mining boot conditions. Slip risk was higher in the overall stiff and overall flexible boot conditions. Variable flexibility and stiffness between the shaft and sole is a better design.